Correlation between Liver Ultrasonography with AST and ALT Value in Suspect Hepatitis - Majdawati, Ana; Gugun, Adang Muhammad (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Liver ultrasonography is frequently recommended in Hepatitis patients. Hepatitis is liver inflammation caused by infection with microorganisms, drugs, and alcohol. Hepatitis causes liver cell damage and sometimes can change the echostructure of ultrasonography. These changes have affected the value of Aspartate Aminotransferase (AST) or Alanine Aminotransferase (ALT). AIM: The study aimed was to identify the correlation of liver ultrasonography with liver function (AST / ALT) in patients with suspected Hepatitis. METHOD OLOGY: The method was a Cross-Sectional approach to identify the relationship of liver ultrasonography, including echostructure, size, edge or surface, portal vein, gall bladder with AST and ALT in patients with suspected Hepatitis. The subjects were from PKU Muhammadiyah Hospital Yogyakarta, 2015-2018, 18-60 years old. They were identified using ALT and AST and proposed ultrasonography of the liver and gallbladder. The samples size consisted of 68 men and 32 women. Liver enzyme and ultrasonography did not know the results of this examination (blind). The relationship between the two variables was analyzed through the Chi-Square. RESULTS: The result was showed a significant relationship between liver ultrasonography, including the echostructure, size, portal vein dilatation with AST and ALT, and p-value for echo structure to AST 0.05 and ALT 0.02. The p-value of liver size revealed an AST of 0.03 and a p-value of a portal venous wall with AST 0.06 and with ALT of 0.02. CONCLUSIONS: There was a significant relationship between echostructure, liver size, and portal vein wall with AST and ALT. The liver surface edge and gallbladder had no significant relationship with AST and ALT.